Literasi Sampah Sisa Makanan Terhadap Warga Perumahan Manyingarri Permai di Desa Pakkabba - Abdul Rahman; Nurlela Nurlela; Mauliadi Ramli (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
A Garbage is one of the environmental problems that has yet to be seen in Indonesia. Garbage is one of the causes of air pollution, water pollution, and soil pollution. The problem of waste is also a concern of the district government, including Takalar Regency, especially the Department of Cleanliness and the Environment. The waste management policy in Takalar Regency is contained in the Takalar Regent's Regulation Number 65 of 2018 concerning Policies and Strategies of the Takalar Regency Government in the Management of Household Waste and Types of Household Waste. As a follow-up to the policy, it is also necessary to have active participation from academics to provide enlightenment to the public about the dangers of waste, especially food waste which is addressed to residents of Manyingarri Housing. The purpose of this service is to invite the public to have knowledge and awareness in reducing the risk of food waste by utilizing it into compost that can be used by farmers who live around the housing complex area. The methods used in this activity are discussion, question and answer, and direct door-to-door visits. This service received an enthusiastic response from the government, community leaders, and the general public, so they hoped that similar activities could be carried out in a sustainable manner.